Study of necrotic apoptosis by pulsed electric field ablation in rabbit left ventricular myocardium - Zhao, Zhihong; Chen, Yonggang; Wu, Bin; Qiu, Gaodong; Hong, Liangjie; Chen, Xinhua; Zhang, Xingwei (Frontiers in Cardiovascular Medicine, 2022)
Objective We investigate the histological damage to myocardial cells in the ablation region of the left ventricular epicardium in rabbits using our self-developed cardiac pulsed electric-field (PEF) ablation instrument and ablation catheter. Methods 48 New Zealand rabbits underwent ablation on the left ventricular myocardium after open-heart exposure with a cardiac arrhythmia PEF ablation device and ablation catheter developed by our research institute. The ablation parameters: biphasic electrical pulses; ±800V; pulse width 10μs; interphase delay 500us. CK, CK-MB, AST, and LDH levels were measured. Masson staining was performed, and TUNEL apoptosis in myocardium tissue was analyzed. Results After PEF ablation, the levels of cardiac enzymes, including CK-MB, CK, and AST, increased significantly, peaking 1–3 days after the procedure. Those of CK and CK-MB increased by 15–20 times but returned to the preoperative level after 2 weeks. Based on general observation, it was found that the myocardium in the ablation area was swollen immediately after PEF ablation. Masson staining analysis revealed that cardiomyocytes were broken and infiltrated by erythrocytes after 6 h. After 1 day, the cells started to experience atrophy and necrosis; by 4 weeks, the myocardial cells were completely replaced by hyperplasia. Apoptosis occurred significantly at 6 h and peaked at 24 h post-ablation, and no significant apoptotic cardiomyocytes were seen after 1 week. Conclusion After PEF ablation, cardiomyocytes showed apoptotic process and dyed, at least partially, through a secondary necrosis, ablation boundary was clear, no island myocardium tissue was seen, the ablation areas were replaced by structurally intact fibroblasts.